Market segmentation tools provide insights into demographic variations in bowel cancer screening uptake. Issue 8 (25th May 2019) - Gavens, Lucy; Whiteley, Leila; Belencsak, Agnes; Careless, Jane; Devine, Shirley; Richmond, Nicola; Muirhead, Andrew
Abstract : Background: The National Health Service Bowel Cancer Screening Programme (NHS BCSP) aims to detect individuals who have precancerous polyps or early stage cancer, when it is easier to treat. To be effective, a screening uptake of at least 52% is required. Variations in uptake by demographic characteristic are reported and the aim of this study was to better understand who participates in the NHS BCSP, to inform action to address inequalities in screening uptake. Methods: Invitation-level data for the Derbyshire population were supplied by the NHS BCSP Eastern Hub for the period 1 April 2014 to 31 March 2016. Data were linked by postal code to the Mosaic Public Sector Segmentation tool. Descriptive analysis using 14 groups and 61 types within Mosaic was undertaken to offer insight into the demographic, lifestyle and behavioural traits of people living in small geographies against their screening uptake, with a particular focus on identifying population groups with an uptake below 52% and so at risk of health inequalities. Results: 180 176 screening invitations were dispatched with an overall uptake of 60.55%. Six Mosaic groups have an uptake below the 52% acceptable level: urban cohesion, rental hubs, transient renters, family basics, vintage value and municipal tenants. These groups are characterised by high levels of social-rented accommodation, multicultural urban communities and transient populations. Conclusion: Segmentation tools offer an effective way to generate novel insights into bowel cancer screening uptake and develop tailored strategies for working with identified communities to increase participation.